Mapping the linkages between agriculture, food security and nutrition in Malawi - Aberman, Noora-Lisa; Meerman, Janice; Benson, Todd (International Food Policy Research Institute, 2015)
Smallholder agriculture is the mainstay of Malawi’s economy. Its importance for livelihoods cannot be overstated. 94 percent of rural residents and 38 percent of urban residents engage in agriculture to some extent (Jones, Shrinivas, and Bezner-Kerr 2014), the vast majority as smallholder farmers with landholdings of less than one hectare. Smallholder crops are primarily maize—which accounted for nearly 80 percent of smallholder-cultivated land in 2011 —followed by cassava and other food crops (FAO 2008; IFAD 2011). These foods are grown for household consumption and for sale at local and regional markets. As such, the Malawian food supply, especially in rural areas where markets are thin with few buying or selling options, is shaped largely by trends in smallholder food-crop production